2014
DOI: 10.1039/c3nj01278f
|View full text |Cite
|
Sign up to set email alerts
|

Microwave synthesis of size-controllable SnO2 nanocrystals for dye-sensitized solar cells

Abstract: A microwave hydrothermal synthesis of size-tunable SnO 2 nanocrystals is achieved by employing a SnCl 4 solution in a mixed ethanol-water solvent. A large increase in ethanol content to over 90%, as well as an increase in SnCl 4 concentration, is the key to successfully obtain highly crystallized and well dispersed SnO 2 particles as large as 26 nm, which can be determined by XRD and HR-TEM observations. Such well ripened SnO 2 crystals exhibit a good performance as photoelectrodes in dye-sensitized solar cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(17 citation statements)
references
References 24 publications
0
16
0
Order By: Relevance
“…This was attributed to the faster electron transport in solvothermal SnO 2 film than co‐precipitation SnO 2 film, as verified by EIS characterization. Asdim et al reported the synthesis of size‐tunable SnO 2 nanocrystals by using microwave hydrothermal method and its integration into DSSC as photo‐anode . High IPCE of around 70% was achieved for DSSC based on 26 nm SnO 2 nanocrystals, resulting in PCE of 1.35%.…”
Section: Photo‐anodementioning
confidence: 99%
“…This was attributed to the faster electron transport in solvothermal SnO 2 film than co‐precipitation SnO 2 film, as verified by EIS characterization. Asdim et al reported the synthesis of size‐tunable SnO 2 nanocrystals by using microwave hydrothermal method and its integration into DSSC as photo‐anode . High IPCE of around 70% was achieved for DSSC based on 26 nm SnO 2 nanocrystals, resulting in PCE of 1.35%.…”
Section: Photo‐anodementioning
confidence: 99%
“…Sufficient light absorption is achieved by the nanocrystalline form of the semiconductor, because a large internal surface area increases the dye concentration in the film per unit device area. Wide band gap MOSs ( > 3 eV) [57], such as TiO 2 [58][59][60], ZnO [61][62][63][64][65][66][67], SnO 2 [60,[68][69][70][71], and Nb 2 O 5 [72][73][74], have been studied more or less extensively and used as photoanode materials for DSSC devices. These MOSs present good stability against photocorrosion, transparency in the major part of the solar spectrum, and good electronic properties [75][76][77][78].…”
Section: Nanoparticles-based Semiconductors (0d Nanostructures)mentioning
confidence: 99%
“…Recently, microwave-assisted synthetic technique has been applied to prepare SnO 2 QDs [17,[50][51][52][53][54][55][56][57]. For examples, Liu et al [57] have synthesized SnO 2 QDs with diameters of 3-5 nm by microwave irradiating the solution of SnCl 4 •5H 2 O and alkaline.…”
Section: Microwave-assisted Synthesismentioning
confidence: 99%
“…Tin dioxide (SnO 2 ), a kind of n-type semiconductor with wide-band-gap (E g = 3.64 eV at 300 K), has very wide applications in the fields of gas sensors [1][2][3][4][5][6][7][8][9][10], lithium-ion batteries (LIBs) [11,12], photocatalytic degradations [13,14] and dye-sensitized solar cells (DSSCs) [15][16][17][18][19], photodetectors [20] and heterojunction diode [21]. The wide applications of SnO 2 are greatly benefited from the synthesis methods in its nanostructured materials with different sizes and novel morphologies.…”
Section: Introductionmentioning
confidence: 99%